Copyright Notice

The following manuscript

EWD578 More about the function “fusc” (A sequel to EWD570)

is held in copyright by Springer-Verlag New York. The manuscript was published as pages 230–232 of

Edsger W. Dijkstra, Selected Writings on Computing: A Personal Perspective, Springer-Verlag, 1982. ISBN 0–387–90652–5.

Reproduced with permission from Springer-Verlag New York. Any further reproduction is strictly prohibited.


16 August 1976EWD 578


More about the function fusc. (A sequel to EWD570)

In EWD570 I introduced the function fusc, given by

fusc(1) = 1,       fusc(2n) = fusc(n),       fusc(2n+1) = fusc(n) + fusc(n+1)     .

Compatible with the second part of that definition we derive from the third part  fusc(0) = 0 . I showed there the following iterative program for the computation of  fusc(N)  —with peven and podd standing for "positive and even" and "positive and odd" respectively—

n, a, b := N, 1, 0;
do peven(n) → a, n := a + b, n / 2
   podd(n) → b, n := b + a, (n-1) / 2
od {fusc(N) = b}

On my last trip through the USA, while lecturing to a Burroughs audience, my audience derived this program after it had decided —after only a few very modest hints!— that a good candidate for an invariant relation would be

P:               fusc(N) = a*fusc(n) + b*fusc(n+1)

The audience arrived at this suggestion after a few simple considerations. The first observation was that

fusc(N) = fusc(n)

would be simple to initialize by means of  n:= N . They quickly saw that this was too simple, and considered

fusc(N) = a*fusc(n)

equally trivially initialized by  n, a := N, 1 ; it was then remarked that initialization would not be complicated by an additive term

fusc(N) = a*fusc(n) + b

as that is initialized by  n, a, b := N, 1, 0 . The observation that for  n = 0  the first term would disappear but that  fusc(n+1) = 1  would then hold suggested, together with the third part of the definition for  fusc  the fully blown-up  P  as given above. Separating the cases

n = 2k:fusc(N)= a*fusc(n) + b*fusc(n+1)
= a*fusc(2k) + b*fusc(2k+1)
= (a+b)*fusc(k) + b*fusc(k+1)
n = 2k+1:fusc(N)= a*fusc(n) + b*fusc(n+1)
= a*fusc(2k+1) + b*fusc(2k+2)
= a*fusc(k) + (a+b)*fusc(k+1)

my audience quickly derived —to its pleasant surprise!— the iterative program given above.

*         *         *

From the above program, two properties of the function fusc follow. The first one is that the value of the function fusc does not change if we invert in the binary representation of the argument all "internal" digits, i.e. all the binary digits between the most- and the least-significant ones. For instance  fusc(19) = fusc(29)  because, in binary 19 and 29 are 10011 and 11101 respectively. This follows from the comparison of the a,b-pairs during those two computations. After the processing of the least significant digit of the arguments, both have  a,b = 1,1 . As a result of the inverted internal digits, the one computation has the role of  a  and  b  interchanged with respect to the other computation. Because the sum of the two values is a symmetric function of its arguments and, as a result of the last —i.e. most-significant—  1  in the argument that sum of  a  and  b  is delivered (in  b ) as the final value, both computations deliver the same result.

The next property is more surprising. (At least, I think so.) Let us try to represent the pair  a,b  by the single value  m , according to the convention

a = fusc(m+1)           b = fusc(m)

In the case of  peven(n)  the operation on  a,b  has the form  a, b := a+b, b  or:

          fusc(m+1), fusc(m):= fusc(m+1)+fusc(m), fusc(m)
:= fusc(2m+1), fusc(2m)

an operation that translates into  m:= 2m . Similarly  a, b := a, a+b  translates into  m:= 2m+1 . Substituting all this in our iterative program we get

n, m := N, 0;
do peven(n) → m, n := 2*m, n/2
   podd(n) → m, n := 2*m+1, (n-1) /2
od {fusc(N) = fusc(m)}

i.e. the fusc-value does not change if we write the binary digits of the argument in the reverse order. For example  fusc(19) = fusc(25)  because 19 and 25 are in binary 10011 and 11001 respectively. I think this second property more surprising!

*         *         *

In a way which does not admit generalization I discovered the equivalence

2|fusc(n) <=> 3|n

i.e.  fusc(n)  is even iff  n  is a multiple of 3. Inspired by a recent exercise of Don Knuth I tried to characterize the arguments  n  such that 3|fusc(n) .

With braces used to denote zero or more instances of the enclosed, the vertical bar as the BNF "or", and the question mark "?" to denote either a  0  or a  1 , the syntactical representation for such an argument (in binary) is


I derived this by considering —as a direct derivation of my program— the finite state automaton that computes  fusc(N)|mod 3 . It was the first time of my life that I did what others have done many times before, i.e. relating a finite state automaton to a grammar. The exercise is up till now only of modest interest; it taught me that division by a fixed factor and (simple!) syntactic analysis are processes that are very closely related to each other, and that insight I think somehow illuminating.

*         *         *

Since the distribution of EW570 it has been discovered that more mathematicians have occupied themselves with the function  fusc  —they only gave it a different name!— a fact that is not surprising in view of its properties. J.J.Seidel and F.L.Bauer have independently pointed out to me that it is no. 56 in Sloane's Dictionary of Integer Sequences, that refers to an article by Rham, Elemente der Mathematik, Vol.2 (1947) pg.95 . It was fun!



Plataanstraat 5
The Netherlands
prof.dr. Edsger W. Dijkstra
Burroughs Research Fellow